If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + -587 = 21 Reorder the terms: -587 + 7b = 21 Solving -587 + 7b = 21 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '587' to each side of the equation. -587 + 587 + 7b = 21 + 587 Combine like terms: -587 + 587 = 0 0 + 7b = 21 + 587 7b = 21 + 587 Combine like terms: 21 + 587 = 608 7b = 608 Divide each side by '7'. b = 86.85714286 Simplifying b = 86.85714286
| 8t-768-13=45 | | 15n=225 | | (18x^2-x-4)=0 | | -8w-744+93=53 | | 6x=28+20 | | 19x^2-8x-20=0 | | 6x+12y=42 | | 22z+593-24=746 | | 4x^2=36x+9 | | 59-d=61 | | 32/4= | | -18b-16938+-588=-840 | | 8n-752+38=78 | | 9n-900+-24=-60 | | 3a^2-10a-131=-6 | | 19x^2-47x+11=0 | | 10n^2+8=198 | | -88=11w | | -84r=0 | | 7=4+3.14 | | 2(5-4y)=10-4y | | 7=4-3.14 | | 4x^2-14x+19=0 | | 4c=-36 | | 7+2=2n-1 | | -16t^2+24t+16=0 | | 45=9a | | 8=2n-1 | | (-7x+4)-(x^2+x-3)= | | (3x+4x^2+3x^3)+(2x-x^2-x^3)-(x+2x^2+4x^3)= | | [7w-6x-4][7w+2x+2]= | | W^2+7w-98=0 |